PLAYING, LIVING TOGETHER AND RESPECTING: PLAYFULPEDAGOGICAL STRATEGIES IN CHILDREN'S SEXUAL EDUCATION AS AN INSTRUMENT FOR SOCIALIZATION AND PROTECTION OF RIGHTS - Almeida, Kathia Susana (Seven Editora, 2026)
Sex education in early childhood has become a highly relevant topic in contemporary educational contexts, especially in light of challenges related to child protection and the development of individuals aware of their rights. This article aims to analyze the role of playful pedagogical strategies in the development of early childhood sex education, considering their contribution to socialization, autonomy building, and violence prevention. The study adopts a qualitative, bibliographic approach, grounded in theoretical frameworks from the sociology of childhood, education, and public policies for child protection. It is based on the assumption that sex education, when properly adapted to children's developmental stages, goes beyond biological aspects and encompasses emotional, social, and cultural dimensions, fostering respect for one's own body and for others. In this context, play emerges as an essential pedagogical tool, enabling meaningful and accessible learning processes for children. Furthermore, the articulation between sex education and the defense of children's rights proves to be crucial in addressing child sexual abuse, particularly in cases where violence occurs within the family environment. The study also engages with concepts from the sociology of childhood, which recognizes children as active social agents, and with Pierre Bourdieu’s notion of habitus, explaining how social dispositions shape behaviors and perceptions from early life. The findings indicate that the integration of playful methodologies into sex education enhances emotional development, strengthens social bonds, and promotes a culture of protection. It is concluded that early childhood sex education, when guided by sensitive and well-structured pedagogical approaches, is an indispensable tool for the comprehensive development of children and for the promotion of a more just and conscious society.